Baseline splenic volume as a biomarker for clinical outcome and circulating lymphocyte count in gastric cancer - Zeng, Ziyang; Liu, Zhen; Li, Jie; Sun, Juan; Ma, Mingwei; Ye, Xin; Yu, Jianchun; Kang, Weiming (Frontiers in Oncology, 2023)
Background The spleen is the largest peripheral lymphoid organ in the body. Studies have implicated the spleen in the development of cancer. However, it is unknown whether splenic volume (SV) is associated with the clinical outcome of gastric cancer. Methods Data of gastric cancer patients treated with surgical resection were retrospectively analyzed. Patients were divided into three groups: underweight, normal-weight and overweight. Overall survival was compared in patients with high and low splenic volume. The correlation between splenic volume and peripheral immune cells were analyzed. Results Of 541 patients, 71.2% were male and the median age was 60. Underweight, normal- weight and overweight patients accounted for 5.4%, 62.3% and 32.3%, respectively. High splenic volume was associated with unfavorable prognosis across the three groups. In addition, the increase of splenic volume during neoadjuvant chemotherapy was not associated with prognosis. The baseline splenic volume was negatively correlated with lymphocytes (r=-0.21, p<0.001) and positively correlated with NLR (r=0.24, p<0.001). In lymphocyte subsets, a negative correlation was found with CD4+T cells (r=-0.27, p=0.041) and NK cells (r=-0.30, p=0.025).